1998
DOI: 10.1079/nrr19980015
|View full text |Cite
|
Sign up to set email alerts
|

Self-organization of foraging behaviour: From simplicity to complexity without goals

Abstract: A herbivore faces challenges while foraging-angoing changes in its physiological condition along with variation in the nutrient and toxin concentrations of foods, spatially and temporally-that make selecting a nutritious diet a vital affair. Foraging behaviours arise from simple rules that operate across levels of resolution from cells and organs to individuals and their interactions with social and physical environments. At all these levels, behaviour is a function of its consequences: a behaviour operating o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
0
3

Year Published

1999
1999
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(61 citation statements)
references
References 149 publications
1
57
0
3
Order By: Relevance
“…The transition from the unfamiliar to the familiar begins at conception and in utero with mother and continues after birth with mother and peers. Lessons learned early in life from a mother create a dichotomy between the familiar and the unfamiliar (novel), which is essential for survival (Provenza, 1995;Provenza et al, 1998 and2003). Animals prefer familiar to novel foods and environments and they prefer to be with companions as opposed to strangers .…”
Section: Trans-generational Transmission Of Self-medicationmentioning
confidence: 99%
“…The transition from the unfamiliar to the familiar begins at conception and in utero with mother and continues after birth with mother and peers. Lessons learned early in life from a mother create a dichotomy between the familiar and the unfamiliar (novel), which is essential for survival (Provenza, 1995;Provenza et al, 1998 and2003). Animals prefer familiar to novel foods and environments and they prefer to be with companions as opposed to strangers .…”
Section: Trans-generational Transmission Of Self-medicationmentioning
confidence: 99%
“…There is disagreement about the quantity of food that is needed to produce sufficient change in internal state to cause a consequent change in diet selection. It has been suggested (Provenza et al 1998) that the short-term systemic fluctuations in the levels of metabolites and hormones that occur during a meal are sufficient to affect the composition of the next meal to be selected. But the evidence cited in favour of this view, which is that of de Jong (1981), is precisely that which refutes the argument.…”
Section: The Role Of Internal State In Diet Selectionmentioning
confidence: 99%
“…For example, previous ecological exposure to PSMs increases tolerance to those PSMs, but may decrease tolerance to novel PSMs (Gustafsson and Hansson, 2004;Sorensen et al, 2005b). Memory of the positive and negative experiences of exceeding thresholds to nutrients and PSMs via conditioned food aversions can also influence foraging phenotypes (Provenza et al, 1998).…”
Section: Foraging Phenotypes: An Integrated View Of Nutrients and Toxmentioning
confidence: 99%
“…It has been widely observed that the quality, quantity, and complexity of nutrients and PSMs and the learned responses to these dietary components can mediate the foraging patterns of herbivores (Amsler, 2008;Behmer, 2009;Hay and Fenical, 1988;Paul and Vanalstyne, 1992;Provenza et al, 1998;Provenza et al, 2003;Simpson and Raubenheimer, 2001). Although the general concepts of pharmacology were introduced to ecologists to explain plant-herbivore interactions 38 years ago (Freeland and Janzen, 1974), the empirical use of pharmacology to understand mechanisms driving foraging patterns in any system is limited (Haley et al, 2008;Magnanou et al, 2009;Marsh et al, 2006b;McLean and Duncan, 2006;Sotka et al, 2009).…”
Section: Pharmacological Mechanismsmentioning
confidence: 99%